FA-CS-MELPH-C343 synthesis, characterization and kinetics of a potential biocompatible, fluorescent and target specific anticancer prodrug - Raguindin, Ricky Kristan M.; Mercado, Candy C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Cancer is a disease-of-interest in research due to its alarming cases and crucial treatment commonly by chemotherapy involving cytotoxic drugs like melphalan (MELPH) that causes adverse effects. Thus, this study aims to synthesize, characterize and study the kinetics of folic acid (FA) adsorbed onto chitosan (CS)-encapsulated MELPH and coumarin 343 (C343) (FA-CS-MELPH-C343) as potential anticancer prodrug that is biocompatible, fluorescent and target specific. It aims to minimize the side effects of melphalan by decreasing the required drug intake and releasing the drug only to specific cancer cells. MELPH molar absorptivity and degradation, MELPH and C343 encapsulation/release, and FA adsorption/desorption kinetics are studied. The synthesis involves MELPH and C343 encapsulation into CS via tripolyphosphate-induced ionic gelation method, then FA adsorption. UV-vis spectroscopy determines MELPH extinction coefficient as 683.72 Lmol-1 cm-1 and its degradation, MELPH and C343 encapsulation/release, FA adsorption/desorption that are both described by Ho-McKay pseudo-second order, and fluorescence intensity that is increased by CS-encapsulation and FA adsorption. Scanning electron microscopy (SEM) images show rounded particle morphology wherein smaller particles tend to coagulate and appear as larger particles, while dynamic light scattering reveal moderate stability with a zeta potential of 34.4 m V and 529.4 nm size of FA-CS-MELPH-C343. Raman spectroscopy confirms the prodrug identity. Because of its encapsulation, release mechanism, and biocompatibility, the FA CS-MELPH-C343 has potential as anticancer prodrug.
Thesis (Bachelor of Science in Materials Engineering)--University of the Philippines Diliman
Keywords: Antineoplastic agents; Cancer -- Treatment